Nutritional Status of Buffaloes in Tribal District Mandla of Central India - Sharma, Pramod; Shukla , Rashmi (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
A participatory field study on nutrient management of buffaloes by resource poor tribal farmers and its correlation with milk production was carried out in Bichhia Block of Mandla District in Central India with 41 buffalo owners in 2015. A 15 point questionnaire was developed to gather information on the feeding management and milk production of buffaloes. The body weight of the buffaloes was calculated by the Schaeffer’s formula. The average body weight of buffaloes was 538 ± 7.5 kg. The average milk production and 4% FCM yield was 5.88 and 8.74 kg, respectively. The total nutrient fed (DCP, TDN) was compared with nutrient requirement. It was found that DCP, TDN, calcium and phosphorus were deficit by 28.00, 19.01, 21.30 and 37.76 %, respectively. It was concluded that the low milk production in buffaloes was due to nutrient deficit ration fed to the lactating buffaloes. Therefore, a massive extension follow up programme for creating awareness on nutrient management of buffaloes should be made.